Analysis of the Influence of Brand Image and Service Quality on Patient Loyalty with Patient Satisfaction as an Intervening Variable: Literature Review - Al Muntazar Bin Saharudin; Mhd Latief Shihab Lubis (Griya Eka Sejahtera, 2026)
Background: The success of an agency in building a brand image depends on the good quality, comfort and status that the agency has provided to consumers. A strong brand image allows agencies to gain direct trust from consumers. Brand image or commonly known as Brand image is the perception formed in the minds of consumers regarding a brand, which reflects the values, identity and personality associated with the product or service. Brand image is also considered a valuable intangible asset (intangible assets) of a company. A positive image allows a company to gain reputation value and competitive advantage. A good image will increase customer satisfaction, service quality, loyalty, and repurchase intentions.Methods: This research is a literature review literature study. The author used the PRISMA systematic review method, which includes merging, filtering, inclusion, and eligibility based on article findings which were then analyzed.Results: The Influence of Brand image and Service Quality on Patient Loyalty with Patient Satisfaction as an intervening variable is not only studied through a direct relationship to all variables, but also an analysis of each variable by examining the influence of brand image on patient satisfaction, the influence of brand image on patient loyalty, service quality on patient loyalty, the influence of service quality on patient satisfaction and the influence of patient satisfaction on patient loyalty.Conclusion: Based on the explanation above, it can be concluded that brand image and service quality influence patient loyalty. This means that patient satisfaction is an important variable in determining whether patients will reuse a given healthcare service